Identifikasi Permasalahan Perkembangan Motorik pada Anak Usia 5-6 Tahun di Wilayah Jakarta Selatan - Dhea Ratuhasanah; Zanizar Jasmine Zahri; Nurfadilah Nurfadilah; Syafriani Afriandita (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2026)
Motor development is an important aspect of early childhood growth that supports learning readiness, social interaction, and independence. However, previous studies have shown that motor development problems are still found among children in Indonesia. This study aims to identify parent-reported indications of gross and fine motor development barriers among children aged 5–6 years in South Jakarta, analyze contributing factors, and examine parental stimulation efforts. The study employed a descriptive survey method using a simple quantitative approach supported by thematic analysis. The participants consisted of 99 parents or guardians of children aged 5–6 years residing in South Jakarta. The findings revealed parent-reported indications of motor development barriers, particularly in tying shoelaces (29%), cutting along patterns (9%), riding a tricycle (7%), showing low interest in physical activities (2%), crawling while going up or down stairs (2%), and catching a ball (1%). The results also indicate that limited stimulation, parenting practices, and characteristics of urban environments may contribute to these barriers. Therefore, collaboration between parents and schools is needed to provide consistent motor stimulation in order to support optimal motor development among young children.